Launching next generation ICT for weather and water information and advice to smallholders in Africa [Abstract only]. - Sharma, Bharat R.; Rebelo, Lisa-Maria; Amarnath, Giriraj; Miltenburg, I. (2013)
We implemented an IFAD-supported project to promote ICT-based technologies for weather, water and crop ?related information and advice to smallholders in Africa. A detailed user need assessment was carried out at four project sites in Ethiopia, Egypt, Sudan and Mali. About 60 farmers at each of the site receive customised information allowing them to plan at the individual field scale not just what to plant and irrigate, but when the weather conditions will be just right for maximum success. Additionally, the farmers in Sudan shall receive forecast on the potential floods. This has hugely empowered the small farmers of the vulnerable communities.